Femoral-Physeal-Sparing ACL Reconstruction With Lateral Extra-articular Tenodesis and Inside-Out Repair of Lateral Meniscus in a Skeletally Immature Patient - Morgan D. Homan DO; Riley Kramer BS; Mark T. Banovetz BS; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2023)
Background: Anterior cruciate ligament (ACL) reconstructions in skeletally immature patients have an increased risk of graft failure and a decreased rate of successful return to sports. Anterior cruciate ligament reconstructions (ACLRs) combined with lateral extra-articular tenodesis (LET) procedures are reported to limit anterolateral rotary instability of the knee, decreasing tension on the ACL graft. However, the open physes found in pediatric patients present unique challenges for ACLR. This video demonstrates a technique to avoid the femoral physis and necessary precautions for performing an ACLR with LET in a skeletally immature patient. Indications: The indications for combined ACLR and LET, as opposed to ACLR alone, mainly center on the risk factors for graft failure. These include the following: posterior tibial slope >12°, revision ACLR, high-grade pivot shift on physical examination, meniscal deficiency, generalized ligamentous hyperlaxity, and-especially pertinent to this procedure-skeletally immature patients. Technique Description: Standard plain radiographs and long-leg alignment films, along with a magnetic resonance imaging (MRI) study, are necessary to assess for malalignment, bone age, and concomitant meniscal and chondral pathology. This technique describes the senior author's preferred technique for pediatric ACLR with LET. The senior author's preferred order of operations includes performing the autologous hamstring graft harvest and LET before performing the diagnostic arthroscopy. This is followed by the intra-articular work including the ACLR. It is also the senior author's preference to perform physeal-sparing femoral tunnels, using fluoroscopy for tunnel placement. Results: Getgood et al reported that an ACLR with an LET in young patients with a high risk of graft failure had a significant reduction in graft rupture compared to an ACLR alone. Furthermore, Noyes et al reported a significantly lower rate of graft failure and a higher rate of return to sports in those who received LET in addition to ACLR compared with those who received ACLR alone. Discussion: An ACLR combined with an LET has been reported to reduce graft failure rates and improve clinical outcomes in high-risk patients. An ACLR with LET may also be considered in skeletally immature patients with appropriate indications and extra precautions to avoid growth arrest or deformity. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.